The pipeline and valve location problem. (1st January 2012) - Laporte, Gilbert; Pascoal, Marta M.B.
This paper, proposes an exact algorithm for the problem of locating a pipeline between two points of a network, as well as a set of safety valves which help control the damage caused by possible spills along the pipeline. A labelling approach is developed to determine simultaneously the optimal pipeline and valve locations, with the objective of optimising an impact measure that depends on the average number of accidents and their cost. Computational experiments on grid and random instances are presented in order to evaluate the algorithm's performance and to compare its results to the solutions provided by sequential approaches.